Enhancing EFL Speaking Skills Through Thematic Comic Strips: An Exploration in a Junior High School Setting - Munir Munir; Sudarwinoto Sudarwinoto; Suhesty Suhesty; Suriama Yaman (ELT Worldwide: Journal of English Language Teaching, 2023)
This study investigates the novel application of comic strips as a pedagogical tool to enhance speaking skills among EFL students in a junior high school setting, with a thematic focus on "Celebrating Independence Day." Drawing from a sample of students from VIII.1 class of UPT SPF SMPN 23 Makassar, the research employed pre-test and post-test measures to gauge the impact of comic strips on speaking proficiency. The findings revealed a significant improvement in students' speaking skills, with the post-test mean score (76.75) surpassing the pre-test mean score (57.02). This increase, backed by a P-value of 0.000, which is smaller than the chosen significance level (α) of 0.05, underscores the efficacy of comic strips as an innovative teaching tool. The results not only highlight the potential of comic strips in EFL instruction but also emphasize the added value of integrating cultural themes into language learning for a richer, more contextualized experience.